The Impact of Corporatisation on the Ottoman Economy: Trade and Industry Oriented Approach (Jurnal Adabiya, 2025)
Joined companies (Anonim Şirketi) are an important sign that the Ottoman Empire was beginning to participate in the global economic process at that time. This was influenced by the industrial revolution and developments in production technology from the west. As part of the reforms of the Tanzimat period led by Sultan Abdülmecid, the Ottoman Empire tried to adopt this new production approach instead of preserving traditional production methods. Therefore, the aim of this study is to analyse the influence of companies in the post-Tanzimat reform period in more depth. As a historical approach, trade development and western industrial orientation in that period will be analysed. The research method used is qualitative, with data collected from various sources and analyzed through descriptive analysis.The findings show that the influence of foreign capital and the establishment of foreign firms such as banks and infrastructure companies had a significant impact on the Turkish economy. However, the economic stability of the Ottoman Empire depended on the trade independence of the companies at that time. Although the potential in that region was very high, it was restricted by the companies established by western powers and the purchase of cheap raw materials from the local population. Moreover, at the beginning of the reform, trade competition still favoured the west, as the local population lacked technological knowledge and skills and had difficulty competing with foreign merchants.ABSTRAKPerusahaan gabungan (Anonim Şirketi) merupakan sebuah penanda bahwa Kekaisaran Turki Usmani mulai berpartisipasi dalam proses ekonomi global pada saat itu. Hal ini dipengaruhi oleh revolusi industri dan perkembangan teknologi produksi dari barat. Sebagai bagian dari reformasi periode Tanzimat yang dipimpin oleh Sultan Abdülmecid, Kesultanan Utsmaniyah mencoba untuk mengadopsi pendekatan produksi baru ini alih-alih mempertahankan metode produksi tradisional. Oleh karena itu, tujuan dari penelitian ini adalah untuk menganalisis pengaruh koosporatisasi pada periode reformasi pasca-Tanzimat secara lebih mendalam. Sebagai pendekatan historis, perkembangan perdagangan dan orientasi industri barat pada periode tersebut akan dianalisis. Metode penelitain yang digunakan ialah kualitatif dengan mengumpulkan data dari berbagai sumber dan melakukan analisa secara deskriptif analisis. Hasil penelitian menunjukkan bahwa pengaruh modal asing dan pendirian perusahaan-perusahaan asing seperti bank dan perusahaan infrastruktur memberikan dampak yang signifikan terhadap perekonomian Turki. Namun, stabilitas ekonomi Kekaisaran Turki Usmani bergantung pada kemandirian perdagangan perusahaan-perusahaan pada saat itu. Meskipun potensi di wilayah tersebut sangat tinggi, namun dibatasi oleh perusahaan-perusahaan yang didirikan oleh kekuatan Barat dan pembelian bahan baku murah dari penduduk lokal. Selain itu, pada awal reformasi, persaingan perdagangan masih berpihak pada barat, karena penduduk lokal tidak memiliki pengetahuan dan keterampilan teknologi dan mengalami kesulitan untuk bersaing dengan pedagang asing.
Keywords: Corporatisation; trade; Industry; Ottoman Empire; Economy effect.